Enzyme‐Free Detection of Glucose with a Hybrid Conductive Gel Electrode. Issue 1 (14th August 2018) - Wustoni, Shofarul; Savva, Achilleas; Sun, Ruofan; Bihar, Eloise; Inal, Sahika
Abstract: Current assays for glucose monitoring rely predominantly on glucose oxidation‐catalyzing enzymes because of the high specificity of enzyme–substrate interactions. Enzymes are however expensive, suffer from instability during fabrication, operation, and storage, and necessitate complex procedures for integration with transducer materials. These challenges, rendering the enzyme‐based sensors disadvantageous for routine glucose monitoring, can be overcome by nonenzymatic sensors. Here, for the enzyme‐free detection of glucose, an electroactive gel is developed via one‐pot polymerization. The functional material is a hybrid of the conducting polymer poly(3, 4‐ethylenedioxythiophene):polystyrenesulfonate and a polyacrylamide gel functionalized with phenylboronic acid. As an electrode, the gel exhibits a specific current response to glucose within the standard concentration range measured in the complex blood‐like medium. When integrated as the lateral, micrometer‐scale gate electrode of an organic electrochemical transistor (OECT), the channel current is proven to be sensitive to the presence of glucose in the measurement solution. The advantage of the OECT‐based sensor compared to the amperometric electrode is its miniaturized form, amplified input signal as well the elimination of a reference electrode. Adaptable to different geometries, this conducting gel exhibits multifunctionality within its soft, gel‐like architecture, that is, mixed ionic and electronic conductivity and glucose‐specific electrical response. Abstract : This work demonstrates, for the first time, an all‐polymer based, nonenzymatic, glucose‐sensitive electroactive material. The conducting gel is fabricated via a single‐step electropolymerization and employed either as an amperometric sensor or as a micrometer‐scale gate electrode of an organic electrochemical transistor. At both configurations, this hybrid material offers selective and sensitive electrical sensing performance at low operation voltages.